Trends in research of exosomes associated with breast cancer over the past decade: a scientometric analysis - Wu, Jiaxin; Zheng, Daitian; Wang, Haiting; Zhou, Zhongming; Yang, Qiuping; Wu, Jinyao; Tian, Huiting; Ji, Zeqi; Chen, Lingzhi; Cai, Jiehui; Chen, Yexi; Li, Zhiyang (Frontiers in Oncology, 2023)
Breast cancer remains a significant global health challenge, accounting for 2.3 million new cases in 2020 and ranking as the most prevalent cancer by incidence and the fourth in cancerrelated mortality worldwide. In China, breast cancer also rapidly increases incidence and burden. The research of exosomes in breast cancer has attracted more and more attention and has a rapid development. Recognizing the pivotal role of exosomes in breast cancer research, we have undertaken a comprehensive scientometric analysis of pertinent scholarly articles published over the past decade to elucidate the current research landscape for researchers.In this study, we gathered all pertinent publications from the Web of Science. Biblioshiny (a web interface for Bibliometrix), VOSviewer software, and CiteSpace software were used to analyze the information on publications, including global trends, countries, institutions, journals, authors, keywords, and citations.Results: A total of 1,239 articles and 625 review articles were retrieved. The annual global publication output has an increased trend in recent decades overall. China contributed the most articles. The publications of the USA had the most total link strength. Nanjing Medical University had the most total link strength. The most relevant source was the International Journal of Molecular Sciences. Tang JH contributed the most articles and had the highest H-index, G-index, and total link strength. The most cited document was "Tumor exosome integrins determine organotropic metastasis", with 2730 citations. The basic themes included "exosomes", "expression", "cells", "identification", "biomarkers", and "serum". The keyword "membrane vesicle" had the strongest bursts. The keywords "target", "biology", "suppressor cell", "molecular mechanism", "tumor Exosomes associated with breast cancer 2 progression", "inhibitor", and "model" appeared as prominent focal points in current research and active areas of exploration.Over the past decade, exosome research in breast cancer has undergone a discernible evolution, shifting from broader investigations of exosome roles to focused exploration of specific pathways relevant to breast cancer. Notably, the emphasis has extended to the clinical application of exosomes as biomarkers and potential therapeutic agents in breast cancer treatment.